A Survey on the Effects of Advertising of Unhealthy Food on the Decision of Students - Olga CERNELEV; Ovidiu TAFUNI (Eastern European Journal of Regional Studies)
The purpose of the research was to assess the effects of advertising of unhealthy food products on student's decision and eating behavior. In the present research participated 272 students aged between 18-29 years from the State University of Medicine and Pharmacy “Nicolae Testemitanu” from the Republic of Moldova. Unfortunately, the findings showed that promotional policy of companies in the food sector have escalated and can influence food product purchase behavior among students.